IMPLEMENTATION OF THE FUZZY LOGIC METHOD TO DETERMINE EMPLOYEE ASSESSMENT - Siregar, Agus Trinanda; Andrianto, Richi; Rahayu Putri, Perra Budiarti (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: Performance assessment is the process of measuring an organization in achieving predetermined goals. Performance assessment can also be interpreted as periodically determining the operational effectiveness of an organization and its personnel, based on the vision, mission and organizational standards that have been previously established. Performance appraisals are carried out between superiors and subordinates, looking at the employee's work results in the last year. Employee performance assessment at the North Padang Lawas Regency PUPR Service still uses a manual system so that the files are not arranged quickly and employee performance assessment still uses calculations with Microsoft Excel. With this problem, the fuzzy logic method is used. The fuzzy method is used to obtain the best employee performance assessment, with 3 criteria to produce the greatest value selected. This research aims to design an employee performance assessment application using the fuzzy method, to obtain recommendations for promotion. The test results of 8 people had sufficient value and 2 people had low value. For low-ranking employees, they will be given sanctions and reprimands by their superiors, while for employees with sufficient value, their performance must be improved to be even better. Keywords: fuzzy logic; performance; assessment; employee;  Abstrak: Penilaian kinerja merupakan proses pengukuran organisasi dalam mencapai tujuan yang telah ditetapkan. Penilaian kinerja dapat juga diartikan sebagai penentuan secara periodik efektivitas operasional suatu organisasi, dan personilnya, berdasarkan visi, misi dan standar organisasi yang telah ditetapkan sebelumnya. Penilaian kinerja dilakukan antara atasan dengan bawahan, melihat hasil kerja pegawai dalam setahun terakhir. Penilaian kinerja pegawai pada Dinas PUPR Kabupaten Padang Lawas Utara masih menggunakan sistem manual sehingga berkas-berkas file tidak tersusun secara rapid dan penilaian kinerja pegawai masih menggunakanperhitungan dengan microsoft excel.Dengan permasalahah tersebut menggunakan metode fuzzy logic. Metode fuzzy digunakan dalam mendapatkan penilaian kinerja pegawai terbaik, dengan 3 kriteria untuk menghasilkan nilai terbesar yang terpilih. Penelitian ini bertujuan untuk merancang aplikasi penilaian kinerja karyawan dengan metode fuzzy, untuk mendapatkan rekomendasi kenaikan jabatan. Hasil tes dari 8 orang memiliki nilai cukup dan 2 orang memiliki nilai rendah. Bagi pegawai yang memiliki nilai rendah akan diberikan sanksi dan teguran oleh atasannya, sedangkan bagi pegawai yang memiliki nilai cukup, kinerjanya harus ditingkatkan agar lebih baik lagi. Kata kunci: fuzzy logic; penilaian; kinerja; pegawai